2000
DOI: 10.1046/j.1365-2648.2000.01346.x
|View full text |Cite
|
Sign up to set email alerts
|

‘I really feel I’ve let him down’: supporting family carers during long‐term care placement for elders

Abstract: This paper considers placing a relative in a nursing home from a carer's perspective. A largely structured, interviewer-administered, questionnaire survey was conducted with 48 carers in the United Kingdom and 54 carers in the United States of America. While the data highlight differences between the two countries, shared experiences emerge which suggest that carers often have to make difficult decisions without adequate support. Implications for practice are considered. The need to develop more robust support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 29 publications
(51 reference statements)
6
66
0
1
Order By: Relevance
“…43,74,75 A number of authors have suggested a range of goals for carer support (see Table 1) but in relation to adopting the caregiving role, two aims appear pre-eminent: to enable family members to exercise a genuinely informed choice as to whether to become a carer or not; to ensure that those who opt to care are adequately supported and fully prepared from an early stage, and that they receive ongoing support sensitive to the changing demands they face.…”
Section: The Goals and Purpose Of Carer Supportmentioning
confidence: 99%
“…43,74,75 A number of authors have suggested a range of goals for carer support (see Table 1) but in relation to adopting the caregiving role, two aims appear pre-eminent: to enable family members to exercise a genuinely informed choice as to whether to become a carer or not; to ensure that those who opt to care are adequately supported and fully prepared from an early stage, and that they receive ongoing support sensitive to the changing demands they face.…”
Section: The Goals and Purpose Of Carer Supportmentioning
confidence: 99%
“…3 Feelings of guilt, doubt, sadness, failure and betrayal (of marital commitment) are reported by informal caregivers of people with dementia in circumstances of decision making, such as the need for institutional long-term care. [3][4][5][6] The percentage of people with dementia being admitted to institutional long-term care differs between countries, which might in part be explained by country differences in the organization of dementia care. Care systems across Europe vary, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…En este sentido, ciertos estudios incluyen la perspectiva familiar para indagar aspectos puntuales de la atención, tales como los problemas durante el periodo de transición al cuidado residencial 11,12,13,14 , los beneficios de los programas institucionales orientados a la família 15,16 , y otras cuestiones relacionadas con la prestación de servicios residenciales (servicios hoteleros, atención individualizada...) 10 , aunque la mayoría de estos estudios se han realizado en el ámbito anglosajón.…”
Section: Introductionunclassified